Human platelet lysate successfully promotes proliferation and subsequent chondrogenic differentiation of adipose‐derived stem cells: a comparison with articular chondrocytes. (9th January 2013) - Hildner, F.; Eder, M. J.; Hofer, K.; Aberl, J.; Redl, H.; van Griensven, M.; Gabriel, C.; Peterbauer‐Scherb, A.
Abstract Fetal calf serum (FCS) bears a potential risk for carrying diseases and eliciting immune reactions. Nevertheless, it still represents the gold standard as medium supplement in cell culture. In the present study, human platelet lysate (PL) was tested as an alternative to FCS for the expansion and subsequent chondrogenic differentiation of human adipose‐derived stem cells (ASCs). ASCs were expanded with 10% FCS (group F) or 5% PL (group P). Subsequently, three‐dimensional (3D) micromass pellets were created and cultured for 5 weeks in chondrogenic differentiation medium. Additionally, the de‐ and redifferentiation potential of human articular chondrocytes (HACs) was evaluated and compared to ASCs. Both HACs and ASCs cultured with PL showed strongly enhanced proliferation rates. Redifferentiation of HACs was possible for cells expanded up to 3.3 population doublings (PD). At this stage, PL‐expanded HACs demonstrated better redifferentiation potential than FCS‐expanded cells. ASCs could also be differentiated following extended passaging. Glycosaminoglycan (GAG) quantification and qRT–PCR of 10 cartilage related markers demonstrated a tendency for increased chondrogenic differentiation of PL‐expanded ASCs compared to cells expanded with FCS. Histologically, collagen type II but also collagen type X was mainly present in group P. The present study demonstrates that PL strongly induces proliferation of ASCs, while the chondrogenic differentiation potential is retained. HACs also showed enhanced proliferation and even better redifferentiation when previously expanded with PL. This suggests that PL is superior to FCS as a supplement for the expansion of ASCs and HACs, particularly with regard to chondrogenic (re)differentiation. Copyright © 2013 John Wiley & Sons, Ltd.